Optimization Of Financial Reporting: Development Of A Computer-Based Financial Reporting System In Accordance With Financial Accounting Standards For Private Entities - Sartono, Sartono; Jaurino, Jaurino; Afif, Ali (Dinasti Publisher, 2025)
Private entities must adapt to the implementation of the Financial Accounting Standards for Private Entities (SAK EP), which will take effect in 2025. The transition from manual financial data processing and the use of the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) to SAK EP presents significant challenges. This study explores the needs and challenges of private entities in optimizing financial reporting. It aims to develop a computer-based financial reporting system aligned with SAK EP by identifying reporting requirements, designing, and implementing an efficient system. The research focuses on improving accuracy, speed, and compliance in financial reporting to enhance competitiveness. A computerized financial information system will help private entities manage data more effectively, reducing human errors and ensuring compliance with SAK EP. Using a qualitative descriptive approach, the study finds that cooperatives still struggle with financial reporting in line with SAK EP, although regulations from the Ministry of Cooperatives and SMEs (Permenkop UKM) already accommodate these standards. To address these challenges, a well-designed financial reporting system is essential to support cooperatives and other private entities in complying with SAK EP while improving reporting efficiency and accuracy.